Conceptualising cosmopolitanism and entrepreneurship through the lens of the three-dimensional theory of power. Issue 3 (10th October 2016) - Mouraviev, Nikolai; Kakabadse, Nada K.
Abstract : Purpose: The paper aims to conceptualise cosmopolitanism drivers from the third-level power perspective by drawing on the Steven Lukes' (1974; 2005) theory of power. Additionally, the paper aims to investigate the relationship between entrepreneurs' cosmopolitan dispositions and habitus, i.e. a pattern of an individual's demeanour, as it was understood by Pierre Bourdieu. Design/methodology/approach: This conceptual paper makes use of Bourdieu's framework (habitus) by extending it to the urban cosmopolitan environment and linking habitus to the three-dimensional theory of power and, importantly, to the power's third dimension – preference-shaping. Findings: Once cosmopolitanism is embedded in the urban area's values, this creates multiple endless rounds of mutual influence (by power holders onto entrepreneurs via political and business elites and by entrepreneurs onto power holders via the same channels), with mutual benefit. Therefore, mutually beneficial influence that transpires in continuous support of a cosmopolitan city's environment may be viewed as one of the factors that enhances cosmopolitan cities' resilience to changes in macroeconomic conditions. Originality/value: The paper offers a theoretical model that allows to enrich the understanding of the power–cosmopolitanism–entrepreneurship link by emphasising the preference-shaping capacity of power, which leads to embedding cosmopolitanism in societal values. As a value shared by political and business elites, cosmopolitanism is also actively promoted by entrepreneurs through their disposition and habitus. This ensures not only their willing compliance with power and the environment but also their enhancement of favourable business conditions. Entrepreneurs depart from mere acquiescence (to power and its explicit dominance) to practicing their cosmopolitan influence by active preference-shaping.